2019
DOI: 10.1080/0284186x.2018.1560498
|View full text |Cite
|
Sign up to set email alerts
|

Changes in health-related quality of life among gynecologic cancer survivors during the two years after initial treatment: a longitudinal analysis

Abstract: Background: While many cancer survivors experience persistent impairments in health-related quality of life (HRQoL) for extended periods of time, others recover soon after treatment. The aim of this research is to assess changes in health-related quality of life in endometrial and ovarian cancer survivors during two years post initial treatment, and to assess clinical and sociodemographic characteristics associated with those changes. Methods: This prospective population-based cohort study includes longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 26 publications
4
17
0
Order By: Relevance
“…In line with our findings, various studies have found that, in patients with endometrial cancer or different cancer types, independent of age, comorbidity was associated with poorer HRQoL at baseline or HRQoL deterioration at follow-up [11][12][13]32]. One previous study from our group reported on the association between changes in HRQoL and clinical and sociodemographic characteristics of patients included in the Rogy Care trial and also described the association between cumulative comorbidity burden and poorer HRQoL [12]. What our study adds to the existing knowledge is a detailed comparison of the association of age and comorbidity with changes in HRQoL and the use of longitudinal data from an age-and gender-matched normative control population for comparison of outcomes.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In line with our findings, various studies have found that, in patients with endometrial cancer or different cancer types, independent of age, comorbidity was associated with poorer HRQoL at baseline or HRQoL deterioration at follow-up [11][12][13]32]. One previous study from our group reported on the association between changes in HRQoL and clinical and sociodemographic characteristics of patients included in the Rogy Care trial and also described the association between cumulative comorbidity burden and poorer HRQoL [12]. What our study adds to the existing knowledge is a detailed comparison of the association of age and comorbidity with changes in HRQoL and the use of longitudinal data from an age-and gender-matched normative control population for comparison of outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Only few studies assessed HRQoL longitudinally in patients with endometrial cancer [12,[33][34][35][36][37]. Most had small sample sizes [33,36], either excluded patients with significant comorbidity or did not report on comorbidity [33][34][35][36], or studied the impact of specific treatment modalities on HRQoL rather than the impact of clinical characteristics [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations